Direct action self-help groups in UK flood risk management - Simm, Jonathan (2015)
This thesis critically evaluates the reasons and extent to which Direct Action Self-Help (DASH) groups are, or can be, viable and an efficacious, efficient and effective means of managing and monitoring Flood and Coastal erosion Risk Management (FCRM) assets.